A new species of larval Caeculisoma (Acari: Erythraeidae: Callidosomatinae) ectoparasitic on insects from China and a revised generic diagnosis - Xu, Si-Yuan; Yi, Tian-Ci; Guo, Jian-Jun; Jin, Dao-Chao (Zootaxa, 2019)
Caeculisoma penlineatus Xu & Jin sp. nov. is described and illustrated based on larvae ectoparasitic on Hemiptera from Chongqing Municipality, Guizhou Province and Hainan Province, China. A modified generic diagnosis of larval Caeculisoma is also provided.